Molecular Docking and ADMET Profiling of Cocoa Pod Husk Methanol-Extract Metabolites as Candidate PBP2a Inhibitors of MRSA - Eka Fitri Yanti; Mohammad Rofik Usman; Cece Furwanti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2026)
The incidence of Methicillin-Resistant Staphylococcus aureus (MRSA) resistant to β-lactam antibiotics continues to increase. MRSA resistance is primarily attributed to the presence of penicillin-binding protein 2a (PBP2a), encoded by the mecA gene. PBP2a is a unique membrane-associated enzyme in S. aureus that catalyzes the transpeptidation step in peptidoglycan biosynthesis, thereby conferring resistance to β-lactam antibiotics. Consequently, the development of novel therapeutic strategies is urgently required to combat resistant infections. An insilico approach utilizing cocoa pod husk (CPH) extract (Theobroma cacao L.) represents a promising alternative for the identification of bioactive compounds with potential anti-MRSA activity. CPH is known to contain a wide range of secondary metabolites with diverse biological properties. This study aimed to predict the PBP2a Inhibitors of compounds present in the methanolic extract of CPH using molecular docking and ADMET analysis. Molecular docking simulations were performed using AutoDock Tools, with PBP2a (PDB ID: 4CJN), retrieved from the RCSB Protein Data Bank, as the target receptor. Prior to docking, physicochemical properties of the ligands were evaluated based on Lipinski’s Rule of Five (RO5) to assess drug-likeness. ADMET profiles were subsequently predicted using the pkCSM web server. The docking results demonstrated that all candidate ligands exhibited negative binding energies (< 0 kcal/mol), indicating favorable binding affinity toward PBP2a and suggesting their potential as antibacterial candidates against MRSA. ADMET prediction results revealed that the majority of metabolites in the methanolic extract of CPH possess favorable pharmacokinetic profiles.